Uplifting the people: three centuries of Black Baptists in Alabama - Fallin, Wilson (Religion and American culture, 2007)
Slaves, Afro-Baptist faith, and Black preachers -- God's gift of freedom -- Church life, expansion, and denominational concerns -- Education, Black nationalism, and sociopolitical concerns -- Theology and leadership -- Protest, growth, and revivalism -- Urbanization and economic self-help -- Between the wars -- Rising militancy -- Protest and reorganization -- Continuity, preservation, and challenge